Pengaruh Likuiditas, Efisiensi Operasional, Tax Planning terhadap Nilai Perusahaan dengan Stabilitas Keuangan sebagai Pemoderasi di Asia Tenggara - Sihar Tambun; Nisa Tiana; Riris Rotua Sitorus (Universitas 17 Agustus 1945 Jakarta, 2026)
This study aims to examine how liquidity, operational efficiency, and tax planning affect firm value. Financial stability acts as a factor that strengthens or weakens the influence of these three variables. This research focuses on food and beverage companies in Southeast Asia. The sample consists of 50 companies, with 10 companies each from Indonesia, Malaysia, Singapore, Thailand, and the Philippines. These companies were selected based on the highest revenue and are listed on their respective stock exchanges during the period 2022 to 2024 using purposive sampling method. To analyze the data, moderated regression analysis method with random effect model was used. The results show that liquidity has a positive impact on firm value, while operational efficiency has a negative effect. Tax planning has no influence on firm value. Financial stability strengthens the impact of operational efficiency on firm value but weakens the influence of liquidity on firm value. Financial stability does not affect the relationship between tax planning and firm value.